An Intelligent System for Engine Fault Detection - Paulraj, M.P., Assoc. Prof Dr. (Malaysian Invention & Design Society (MINDS), 2010)
Dr. Paulraj M. P. and his team won gold at ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.